Routledge Handbook of International Human Rights Law - Sheeran, Scott; Rodley, Sir Nigel (Taylor & Francis, 2013)
The Routledge Handbook of International Human Rights Law provides the definitive global survey of the discipline of international human rights law. Each chapter is written by a leading expert and provides a contemporary overview of a significant area within the field. As well as covering topics integral to the theory and practice of international human rights law the volume offers a broader perspective though examinations of the ways in which human rights law interacts with other legal regimes and other international institutions, and by addressing the current and future challenges facing human rights. Providing up-to-date and authoritative articles covering key aspects of international human rights law, this book work is an essential work of reference for scholars, practitioners and students alike. Chapter 35 of this book is freely available as a downloadable Open Access PDF under a Creative Commons Attribution-Non Commercial-No Derivatives 3.0 license. https://www.routledgehandbooks.com/doi/10.4324/9780203481417.ch35